2019
DOI: 10.1007/s12053-019-09777-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of apps to promote energy saving: a study of smart meter–related feedback in the Netherlands

Abstract: Feedback systems with direct feedback have shown to be effective in stimulating households to change their energy consumption levels. This research is one of the first to explore the use of apps to influence household energy use. Compared to dedicated in-home displays, smartphone/tablet apps provide a low-cost and simple design solution for making energy feedback available. This research consisted of three studies conducted with different samples within a selection of households where a smart meter was install… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Even though there are no reports of long-term results on how to sustain the accomplished energy savings, many works have identified that, without proper engagement strategies, once habituation sets in (after as little as four weeks), there is a considerable loss of interest from the end-users in the feedback devices (e.g., [85][86][87][88]). However, it is evident from the literature that, through visualizing smart meter data in a timely and intuitive way, consumers become increasingly literate in understanding their domestic energy consumption, and in particular on how unintentional behavior can lead to unnecessary consumption [89,90].…”
Section: Providing User Feedbackmentioning
confidence: 99%
“…Even though there are no reports of long-term results on how to sustain the accomplished energy savings, many works have identified that, without proper engagement strategies, once habituation sets in (after as little as four weeks), there is a considerable loss of interest from the end-users in the feedback devices (e.g., [85][86][87][88]). However, it is evident from the literature that, through visualizing smart meter data in a timely and intuitive way, consumers become increasingly literate in understanding their domestic energy consumption, and in particular on how unintentional behavior can lead to unnecessary consumption [89,90].…”
Section: Providing User Feedbackmentioning
confidence: 99%
“…In research on the use of smart meter-related feedback applications to stimulate energy conservation, which have similarities with our control condition, the Powersaver Energy Dashboard, inconsistent outcomes are reported. In a study of Geelen et al [23] a large sample of Dutch households (n = 519) were divided into an intervention group that had an energy dashboard and control group that did not have that. Results show no significant difference in reduction in electricity and gas consumption between both groups over a long period.…”
Section: Related Workmentioning
confidence: 99%
“…), each one with its own interface and possible additional options besides the standard energy monitoring, such as user alert in case of energy over-consumption, provision of energy tips, etc. (Geelen et al, 2019 [23]) 1 . To the best of our knowledge, the only contribution on the usage of smart energy apps is that one of Geelen et al (2019) [23], who carried out a quasiexperiment in the Netherlands to assess whether the provision of a smart app monitoring system to a treatment group effectively led to energy savings compared to a non-treated group 2 .…”
Section: Introductionmentioning
confidence: 99%